Adaptasi Penggayaan Eklektik pada Furnitur di Cafe dan Restoran Batik Keris Solo - Maximillian, Arnold; Chrisswantra, Freddy; Jonatan, Lisa (Program Studi Desain Interior Unikom, 2022)
The application of eclectic style to the furniture in the Batik Keris Solo’s cafe and restaurant is one way to form interior atmosphere of the room. The formation of interior atmosphere is adjusted to the heritage building styling in the city of Solo. This Batik Keris’s cafe and restaurant building has been planned using eclectic styling touch that mixes several styles into the space. To form the atmosphere of the space, it is necessary to arrange various interior elements, one of them is furniture, which is considered to be able to provide a visual appearance of the interior of the space in accordance with the main stylistic concept. In this study, the research team tried to focus the analysis on furniture objects that were applied to the interior of heritage buildings as the formation of a space atmosphere. This research was conducted by applying a descriptive qualitative method by conducting studies and direct analysis on furniture objects that were applied as interior elements at Café Batik Keris Solo. Based on the analysis process, it can be seen the application of eclectic style in the furniture in the room. Keywords:Eclectic; Furniture; Heritage; Ambiance